失范社会之女性视角 ：解读张曦娜小说 = Anomie in feminine writing : a study of Teoh Hee La’s fiction - 陈佳琪 Tan, Jia Qi (2019)
后殖民时期的新加坡社会急速地发展，从独立至工业时代，再逐渐转向 国际舞台，有望成为国际大都市。这迅速的社会变迁促使了新加坡华文教育的改革、 英语至上、贫富悬殊等社会问题。曾经的社会规范已失效，而如今社会仍在建立一套 新的社会规范，导致了社会出现失范的状态。张曦娜的小说所关注的便是处在那失范 社会中的新加坡华族同胞。她笔下的人物面对社会失范，陷入无奈与无助的困境时， 往往选择无声的抗议，如自杀、涂鸦等异常行为。本文以张曦娜小说为研究文本，借 助社会学中的失范社会为背景，分析张曦娜作为女作家的女性政治社会的新视角。 In post-colonial Singapore, society has developed rapidly from pre-independence to industrial era. It then gradually navigated itself towards the global stage and it is well on its way to becoming a cosmopolitan society now. However, this rapid social change has brought about various social issues such as Singapore’s Chinese education reform, the supremacy of English, as well as the disparity between the rich and the poor. The mismatch of norms between the society and its people has led to anomie in society. Teoh Hee La’s novels revolve around this group of people, especially the Chinese community in Singapore. One may often find Teoh’s fictional characters choose silent protects such as suicide and vandalism when facing anomie. Using Teoh’s novels as the research subject and anomie theory from sociology, this thesis seeks to analyse Teoh’s feminine sociopolitical writing as a female writer.